A STM-based analytical model for predicting load capacity of deep RC beams with openings. (December 2021) - Karimizadeh, Hamid; Arabzadeh, Abolfazl
Abstract: Deep reinforced concrete beams constitute one of the most important structural members carrying large loads in long span structures that have been less investigated than ordinary beams due to their unconventional behavior. Due to their excessive height, deep beams often pose problems for the proper housing of mechanical and electrical installations that occupy rather large spaces or plumbing systems that pass through structural elements. As a remedy, openings are often needed in such beams that not only serve as a practical provision to house installations but also offer architectural advantages in the structure. Despite these advantages, the openings have serious adverse repercussion on the load-carrying capacity of the beams which, if not properly addressed, might cause grave damages to the structure. The present study introduces an analytical model based on the strut-and-tie method for estimating load-carrying capacity in simply-supported deep RC beams with rectangular or circular openings. The proposed model is capable of independently considering each of the different failure modes including that due to web crippling under load-bearing support sheets as well as flexural and shear failures to identify the dominant failure before it determines the failure mode of the specimen and to estimate, subsequently, the pertinent load-carrying capacity. Being based on the strut-and-tie method, the model relies for its accuracy on the accurate analysis of the strut model. Comparison of the model results and experimental measurements reported elsewhere reveals the accuracy of the proposed model in estimating the load-carrying capacity of deep RC beams. Verification of the model using measured results reported in the literature indicates mean predicted to measured load-carrying capacity ratios of 0.91 and 0.97 for beams with and without openings, respectively.